2020
DOI: 10.18203/2320-6012.ijrms20203462
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and pattern of geriatric limb fractures in Ibadan, Nigeria

Abstract: Background: Individuals within the geriatric age group sustained different types of fractures as such the need to determine the incidence and pattern of limb fractures among patients 65 years and above admitted through the accident and emergency department of the University College Hospital Ibadan.Methods: A retrospective hospital-based study in which patients 65 years and above admitted through the accident and emergency department of the University College Hospital Ibadan over a 42-month period were involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…It is possible that more females may present with more orthopaedic trauma with increasing age than men, probably because of depleting hormones from menopause. In our study, ground-level fall (GLF) was the commonest mechanism of injury, similar to some other reports [10]- [17]. The possible reasons include reduced balance alongside continuing physiologic changes resulting in impaired vision and hearing, decreased motor strength, cognitive impairment, and medications for comorbidities [18].…”
Section: Discussionsupporting
confidence: 84%
“…It is possible that more females may present with more orthopaedic trauma with increasing age than men, probably because of depleting hormones from menopause. In our study, ground-level fall (GLF) was the commonest mechanism of injury, similar to some other reports [10]- [17]. The possible reasons include reduced balance alongside continuing physiologic changes resulting in impaired vision and hearing, decreased motor strength, cognitive impairment, and medications for comorbidities [18].…”
Section: Discussionsupporting
confidence: 84%
“…18 Previous studies done in our center among pediatrics and geriatric patients showed that fractures involving the upper extremity accounted for 62.31% and 23.47% respectively among patients that presented at the accident and emergency department. 20,21 This lower incidence of humeral fractures observed in this study may be due to a higher incidence of fracture involvement in the other bones of the upper extremity such as the radius and the ulnar bone, the scapular and the bones in the hand.…”
Section: Discussionmentioning
confidence: 54%